Possibility of application of glycerol for selection of polyurethane foam systems compositions - Pielichowski, J.; Marek, M.; Prociak, A. (Polimery, 2022)
The two-stage method of preparation of polyols based on soybean oil, with the use of either glycerol or ethylene glycol as hydrogen atom donors in the reaction of epoxy ring opening, was described. At the first stage the unsaturated fatty acids were oxidized under the influence of acetic acid/hydrogen peroxide system to obtain epoxy derivatives. Then epoxy ring opening has been done using one of two donors mentioned. There were determined the chemical and physicochemical properties of soybean polyols obtained (Table 2) which were used for the preparation of rigid polyurethane (PUR) foams (Table 1). The courses of foaming (times of start, gel and tack-free - Table 3) and useful properties (density, heat transfer coefficient, closed cells content, compressive strength - Table 4, Fig. 2) were compared for three types of foams. One of them was control one (with use of commercial polyols) and two were prepared from the compositions in which soybean polyol, prepared with use of either glycerol or ethylene glycol, constituted 50 % of polyol components. The foam prepared with glycerol shows clearly better useful properties than that one prepared with ethylene glycol, nearly so good as a control one. The results show the possible direction of application of glycerol obtained as a by-product in biofuels’ production.